2023
DOI: 10.3389/fbioe.2023.1245897
|View full text |Cite
|
Sign up to set email alerts
|

Porous biomaterial scaffolds for skeletal muscle tissue engineering

Natalie G. Kozan,
Mrunmayi Joshi,
Sydnee T. Sicherer
et al.

Abstract: Volumetric muscle loss is a traumatic injury which overwhelms the innate repair mechanisms of skeletal muscle and results in significant loss of muscle functionality. Tissue engineering seeks to regenerate these injuries through implantation of biomaterial scaffolds to encourage endogenous tissue formation and to restore mechanical function. Many types of scaffolds are currently being researched for this purpose. Scaffolds are typically made from either natural, synthetic, or conductive polymers, or any combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 283 publications
0
1
0
Order By: Relevance
“…Irene Buj-Corral et al [ 50 ] found that high surface roughness of scaffolds was conducive to bone integration. Pore size is essential for the formation of bone tissue, and a pore size more than100μm is conducive to the migration and proliferation of osteoblasts and mesenchymal cells [ 51 ]. The suitable porosity of scaffolds in bone tissue engineering is 30–90 % [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Irene Buj-Corral et al [ 50 ] found that high surface roughness of scaffolds was conducive to bone integration. Pore size is essential for the formation of bone tissue, and a pore size more than100μm is conducive to the migration and proliferation of osteoblasts and mesenchymal cells [ 51 ]. The suitable porosity of scaffolds in bone tissue engineering is 30–90 % [ 52 ].…”
Section: Discussionmentioning
confidence: 99%